Detection of Genetic Variability in Borrelia miyamotoi (Spirochaetales: Spirochaetaceae) Between and Within the Eastern and Western United States. Issue 6 (6th May 2021) - Hojgaard, Andrias; Osikowicz, Lynn M; Maes, Sarah; Eisen, Lars; Eisen, Rebecca J
Abstract: Borrelia miyamotoi is a hard tick-associated relapsing fever spirochete that is geographically widespread in Ixodes spp. (Acari: Ixodidae) ticks, but typically occurs at low prevalence. Genetic variability has been described among strains derived from Asia, Europe, and North America, and among tick species that carry the infection, but little variability has been described within foci or tick species. Capitalizing on access to B. miyamotoi nucleic acid extracted from host-seeking Ixodes scapularis Say or Ixodes pacificus Cooley & Kohls from 16 states, we explored genetic variability based on sequence analysis of four amplicons described herein. Consistent with previous studies, we detected significant genetic differences between strains derived from I. scapularis (eastern United States) and I. pacificus (western United States) and identified two distinct sequences in the western United States (Am-West-1 and Am-West-2). Unique to this study, we identified two distinct sequences in the eastern United States (Am-East-1 and Am-East-2). Based on the 161 samples we analyzed, Am-East-1 was the only type represented in 50 B. miyamotoi -infected ticks collected from the Northeast (Vermont, Maine, New York, Connecticut, and Rhode Island), whereas ticks collected from the North-Central and Mid-Atlantic states harbored B. miyamotoi comprised of both Am-East-1 and Am-East-2. Further studies are needed to better characterize the phylogeography of B. miyamotoi and to discern if there are biologically meaningful differences among sequence types. To facilitate further exploration, we developed a polymerase chain reaction (PCR) assay designed to differentiate Am-East-1, Am-East-2, and Am-West sequence types without having to sequence the amplicon.